STRATEGI PENGEMBANGAN PENGELOLAAN BERKELANJUTAN PADA KAWASAN KONSERVASI LAUT GILI SULAT : SUATU PENDEKATAN STAKEHOLDERS - Abubakar, Abubakar (Bumi Lestari; Vol 10 No 2 (2010), 2010)
The aims of this research are (a) to design scenario of strategy on management development of Gili Sulat ocean conservation zone, which are integrated and sustainable (b) to predict economic, social, and ecology impacts on sustainable management of Gili Sulat ocean conservation zone. The research has been conducted in Gili Sulat ocean conservation zone, East Lombok by using survey, observation, and stakeholders’ participatory methods. The collected data have been analyzed by using laboratory and trade-off analysis. The result indicates that : (1) The scenario of management development of sustainable Gili Sulat ocean conservation zone is C scenario (75 % from potential useful zone) (2) The estimation of sustainable economic impacts are on Gross Domestic Regional Product (GDRP), total production, income, and export value as follows Rp. 840,360,768; 81,528 kg; Rp. 416, 471, 684; and US $ 94,125. (3) The estimation of sustainable social impact are on workforce, i.e. 10,620 men days and informal sector development with score 41. (4) The estimation of sustainable ecology impact are on BOD (biological oxygen demand), Nitrogen (NO3), Phosphor (PO4), coral reef quality, and mangrove forest quality as follows: 0.560 ppm; 0.028 ppm; 2.946 ppm; score 29; and score 33.
Keywords: strategy; impact; sustainable; stakeholders